(untitled) (Research, Society and Development, 2021)
Objective: Investigate hospitalizations due to stress in the southern states of Brazil from January 2009 to December 2018. Methodology: Records were collected from the SIH / SUS (Hospital Internment System of the Unified Health System) files on the electronic platform of the Department of Informatics of the Unified Health System (DATASUS), referring to hospitalizations whose main diagnosis contained in chapter V of the ICD - 10 belonged to the category F43 “Reactions to “stress ” severe and adaptation disorders” and subcategories. The time trend was assessed by joinpoint regression (version 3.4.2.) And geospatial analysis using Quantum Gis software (QGIS), version 2.16. Results: Paraná, Santa Catarina and Rio Grande do Sul presented a downward trend with Annual Percentage Change (APC) values ​​of -14.7, -6.2 and -15.8, respectively. The female gender was more incident, with the exception of 2013 and 2017. Separating F43 hospitalizations into subcategories, F43.0 (Acute reaction to “stress”) was the main cause of hospitalization due to stress (4.27). The spatial analysis showed 57 High-High municipalities (p <0.05). Conclusion: The data obtained suggest that with the implementation of Ordinance No. 3,088 of December 23, 2011, the number of cases per hospitalization due to stress decreased.